Solvent fractions of Vitellaria paradoxa root extract suppress phenylhydrazine-mediated jaundice in Wistar rats - Daniel Abu Anyebe; Abdullahi Aliyu Turaki; Abdulrahman Bashir Yusuf; Ufuoma Bigila Shemishere; Musa Idu Okwanya; Yahaya Tajudeen (Future Journal of Pharmaceutical Sciences, 2024)
Abstract Background In the first few days of life, jaundice has continued to be a major health concern. It typically manifests as a yellowing of the skin, mucous membranes, and sclera as a result of bilirubin deposition from excessively high concentrations in the body. It affects 80% of preterm and 60% of term new-borns within the first seven days of life, which is of great concern. According to the World Health Organization, the widespread acceptance of traditional medicines can be attributed to their accessibility and affordability. In West African arid savannah, there is a tree called Vitellaria paradoxa (Sapotaceae) that grows naturally. This well-known herb has numerous applications in medicine. Various plant components, including the leaves, roots, seeds, and fruit, have all been used in traditional medicine to cure a variety of illnesses. The purpose of this study is to objectively ascertain the efficacy of V. paradoxa root extracts on jaundice. Rats given phenylhydrazine (PHZ) to induce hyperbilirubinemia were orally administered ethylacetate, n-butanol, n-hexane, and aqueous fractions. Result Results indicated the presence of terpenoids, flavonoids, and phenol. n-hexane and ethylacetate fractions showed activity against jaundice in rats. This observation was due to the fact that they significantly improved all biomarkers that were examined, namely body weight change, liver function parameters (total bilirubin, direct bilirubin, aspartate aminotransferase, albumin, and total protein), haematological parameters (white blood cells, haemoglobin, red blood cells, haematocrit, and platelets), and antioxidant enzymes (superoxide dismutase and malondialdehyde). Conclusion n-Hexane and ethylacetate fractions of the extract showed significant activity against PHZ-induced jaundice in rats. However, n-hexane fraction was the most active fraction.